# Answer to Question #24103 in Algebra for Mike

Question #24103

Factor completely:

x^4 - 6x^2 y^2 + 9y^4

x^4 - 6x^2 y^2 + 9y^4

Expert's answer

Let's use the perfect square formula:

x^4 - 6x²y² + 9y^4 = (x² - 3y²)

And now let's use the difference of two squares formula:

(x² - 3y²) = (x - √3y)(x + √3y).

Now factorization is complete. Therefore,

x^4 - 6x^2 y^2 + 9y^4 = (x - √3y)

x^4 - 6x²y² + 9y^4 = (x² - 3y²)

^{2}And now let's use the difference of two squares formula:

(x² - 3y²) = (x - √3y)(x + √3y).

Now factorization is complete. Therefore,

x^4 - 6x^2 y^2 + 9y^4 = (x - √3y)

^{2}(x + √3y)^{2}Need a fast expert's response?

Submit orderand get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

## Comments

## Leave a comment